THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ABILITY OF THE THIRD YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UNIVERSITAS RIAU - Ramadhaniarty, Maqliga; Azhar, Fadly; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The main, objectives of the study are to find out; 1) the students’ grammar mastery, 2) the students’ writing ability and 3) the correlation between grammar mastery and writing ability. The population of the study is 104 third year students, the sample is 22 students by using the cluster random sampling technique. The data were collected through 40 questions (grammar test) about students’ grammar (Grammar Mastery) and 1 question (essay) about students’ writing ability. The result of the test was analyzed by using the Pearson product moment in SPSS version 23. From the analysis, it was found that the third year students of English Study Program of FKIP Universitas Riau were at a good level in their grammar mastery, meanwhile the students’ writing ability mean score 73.33. The correlation between both variables was in high correlation with the level was 0.720. However, building motivation and mindset about having a good grammar mastery is essential to be recommended because it is very useful to develop students’ English skill and help them to face some tests which correlate with students’ writing ability.Key Words: Correlation, Grammar Mastery, Writing Ability